Implementation of the Blue Economy Policy in Probolinggo City for the Development of the Creative Economy of Processed Fisheries and Marines - Siti Marwiyah; Nurul Jannah Lailatul Fitria (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
The challenge of developing the blue economy in Probolinggo City is to maximize the utilization and processing of marine and fishery products without damaging the marine and aquatic ecosystems. For this reason, special policies are implemented in the management of the marine and fisheries sector with special reference to marine and fisheries products as the leading sector, not only as food security for local communities but also as an economic and tourism sector that can be developed in Probolinggo. City Public policy is needed to implement the blue economy in Probolinggo City. This study aimed to examine the application of the